Classics of Russian literature - Weil, Irwin; Teaching Company (Chantilly, VA : Teaching Co., 2006)
Thirty six lectures by Irwin Weil, of Northwestern University, exploring the history of Russian literature from its origins through the twentieth century.
pt. 1. (discs 1-2) (lectures 1-12). Origins of Russian literature ; Curch and the folk in Old Kiev ; Aleksandr Sergeevich Pushkin, 1799-1837 ; Exile, rustic seclusion, and Onegin ; December's uprising and two poets meet ; Poet contrasts talent versus mediocrity ; St. Petersburg glorified and death embraced ; Nikolai Vasil'evich Gogol', 1809-1852 ; Russian grotesque, overcoats to dead souls ; Fedor Mikhailovich Dostoevsky, 1821-1881 ; Near mortality, prison, and an underground ; Second wife and a great crime novel begins -- pt. 2. (discs 3-4) (lectures 13-24). Inside the troubled mind of a criminal ; Generation of the Karamazovs ; Novelistic presence of Christ and Satan ; Lev Nikolaevich Tolstoy, 1828-1910 ; Tale of two cities and a country home ; Family life meets military life ; Vengeance is mine, saith the Lord ; Family life makes a comeback ; Tolstoy the preacher ; Ivan Sergeevich Turgenev, 1818-1883 ; Stresses between two generations ; Anton Pavlovich Chekhov, 1860-1904 -- pt. 3. (discs 5-6) (lectures 25-36). M. Gorky (Aleksei M. Peshkov), 1868-1936 ; Literature and revolution ; Tribune - Vladimir Maiakovsky, 1893-1930 ; Revolution makes a u-turn ; Mikhail Aleksandrovich Sholokhov, 1905-1984 ; Revolutions and civil war ; Mikhail Mikhailovich Zoshchenko, 1895-1958 ; Among the godless - religion and family life ; Boris Leonidovich Pasternak, 1890-1960 ; Poet in and beyond society ; Aleksandr Isaevich Solzhenitsyn, born 1918 ; Many colors of Russian literature.
DVD
Professor Irwin Weil.
In three parts (containers). Each part consists of twelve lectures on two discs.
Keywords: Dostoyevsky, Fyodor, -- 1821-1881 -- Criticism and interpretation; Tolstoy, Leo, -- graf, -- 1828-1910 -- Criticism and interpretation; Russian literature; Russian literature -- 19th century -- History and criticism; Russian literature -- 20th century -- History and criticism